S-Coprime Submodules - Hadi, Inaam M.A.; Khalaf, Rasha I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduce and study the concept of S-coprime submodules, where a proper submodule N of an R-module M is called S-coprime submodule if M N is S-coprime Rmodule. Many properties about this concept are investigated.